Creative entrepreneurship and urban space: Exploring the location preferences of creative professionals in Αthens during the economic recession - Lavanga, Mariangela; Loots, Ellen; Konomi, Maria Adela; Avdikos, Vasilis; Iliopoulou, Eirini (The Greek Review of Social Research, 2020)
Academic scholarship has scrutinised the triangle connecting creativity, locality and economic activity in three ways. First, the clustering of firms has been found to promote creativity in an urban environment (cf. clustering theories). Second, and indicating an inverse course of action, creative individuals have been found to foster the economic growth of cities by attracting employers to places where the former want to reside (cf. creative class theory). Third, the specific attributes of a location, in particular urban environments, have been shown to have a positive impact on individual creativity. Our study adds to this fascinating liaison by exploring: the economic and non-economic features that lead to designers establishing their businesses in Athens’ city centre; and the perceived direct and indirect benefits of these locational factors in relation to the creative labour of these entrepreneurs. In this way, we merge micro and macro perspectives on the relationship between creative entrepreneurship and place, but in a potentially experimental setting, given that the urban fabric in Athens had to be reconstructed after it experienced economic and social turbulence following the 2008/2009 economic crisis and the austerity measures that were the result.